α-sulfonyl radical initiated intramolecular tandem radical cyclization: Stereochemistries of a pair of doubly cyclized products - Lindsay T. Byrne (2018)
Room-temperature single-crystal X-ray structure determinations are recorded for trans-1,2,3,3a,9,9a-Hexahydro-cyclopenta[b]-1-benzothiapyran-4, 4-dioxide and its 3a-methyl analogue, minor products of the α-sulfonyl radical-initiated intramolecular tandem radical cyclization of H2C=CH(CH2)CRBrSO2Ph (R = H, CH3), confirming the assigned structures and rigorously establishing the trans relationship at the ring junctions.